2020
DOI: 10.1007/s42860-020-00101-w
|View full text |Cite
|
Sign up to set email alerts
|

Naproxen/Layered Double Hydroxide Composites for Tissue-Engineering Applications: Physicochemical Characterization and Biological Evaluation

Abstract: Injured bone tissues can be healed with bone grafts, but this procedure may cause intense pain to the patient. A slow and localized delivery of nonsteroidal anti-inflammatory drugs (NSAIDs) could help to reduce the pain without affecting bone regeneration. The objective of the present study was to use [Mg-Al]-layered double hydroxide (LDH) as a matrix for controlled release of sodium naproxen (NAP). This system could be applied in biomaterial formulations (such as bone grafts) to achieve a local delivery of na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In order to alleviate the intense pain during bone grafting procedures, Bernardo et al prepared sodium naproxen (NAP, an anti-inflammatory drug)-intercalated MgAl-LDH. 457 The release of NAP was monitored under simulated physiological conditions, and the results showed that free NAP dissolved immediately, while NAP intercalated into LDH was released slowly over 48 h. This could potentially be applied to effectively relieve pain for an extended period of time from a single dose.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…In order to alleviate the intense pain during bone grafting procedures, Bernardo et al prepared sodium naproxen (NAP, an anti-inflammatory drug)-intercalated MgAl-LDH. 457 The release of NAP was monitored under simulated physiological conditions, and the results showed that free NAP dissolved immediately, while NAP intercalated into LDH was released slowly over 48 h. This could potentially be applied to effectively relieve pain for an extended period of time from a single dose.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Also, Berber et al [255] intercalated naproxen (NP) and flurbiprofen (FB) into MgAl-LDH via reconstruction and coprecipitation techniques to prepared NP-LDH and FB-LDH nanocomposites and found that the hydrophilic surface area of drug-LDH composites increased the water penetration into the drug components. In the research of Bernardo et al, [250] MgAl-LDH was successfully combined up to 80% w/w of NP by the structural reconstruction route. Pharmacokinetic studies showed a mild NP release, indicating the potentiality of MgAl-LDH for local and sustained convey of naproxen at adequate concentrations.…”
Section: Ldhs Loaded With Nsaidsmentioning
confidence: 99%
“…Apart from reducing adverse effects of systematic medication, the double‐layer structure of LDHs can protect the loaded NSAIDs from degradation or first‐pass elimination before being transported to orientated sites thus enhancing their pharmacological effects. [ 250 ] NSAIDs encapsulated between the layers of LDHs can also effectively reduce the damage of drugs to gastric mucosa because of the anti‐acid property of LDHs. [ 251 ] During the last decade, LDHs incorporated with different NSAIDs through various technologies such as ion exchange and coprecipitation have been widely researched.…”
Section: Ldhs For Analgesiamentioning
confidence: 99%